Non-Linear Mixed Logit - Steffen Andersen; Glenn W. Harrison; Arne Risa Hole; Elisabet E. Rutström (Copenhagen Business School (CBS), Department of Economics, 2010)
We develop an extension of the familiar linear mixed logit model to allow for the direct estimation of parametric non-linear functions defined over structural parameters. A classic application is the estimation of coefficients of utility functions to characterize risk attitudes. There are several unexpected benefits of this extension, apart from the ability to directly estimate structural parameters of theoretical interest.
hdl:10398/8171
Keywords: C10; 330; utility functions; risk attitudes; utility theory